2004
DOI: 10.1007/s00439-004-1117-7
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the isolated population of the Faroe Islands investigated using Y chromosomal markers

Abstract: Historical, archaeological and linguistic sources suggest that the ancestors of the present day population in the Faroe Islands may have their origin in several different regions surrounding the North Atlantic Ocean. In this study we use binary and microsatellite markers of the Y chromosome to analyse genetic diversity in the Faroese population and to compare this with the distribution of genotypes in the putative ancestral populations. Using a combination of genetic distance measures, assignment and phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…While it is possible that genetic drift has affected gene frequencies so that our estimates of admixture no longer accurately reflect the composition of founder populations, it seems unlikely to be coincidental that the overall proportion of Scandinavian ancestry for these three locations decreases in harmony with geographic distance from Scandinavia. Admixture analysis (using mr) of recently published Y-chromosome data from the Faroe Islands (Jorgensen et al, 2004) also provides evidence for a trend of increased Scandinavian patrilineal ancestry in regions further from the British Isles. The estimated Scandinavian genetic component of the Faroese samples is 87% (N ¼ 89, k ¼ 26), a higher figure than for either Shetland or Orkney.…”
Section: Discussionmentioning
confidence: 83%
“…While it is possible that genetic drift has affected gene frequencies so that our estimates of admixture no longer accurately reflect the composition of founder populations, it seems unlikely to be coincidental that the overall proportion of Scandinavian ancestry for these three locations decreases in harmony with geographic distance from Scandinavia. Admixture analysis (using mr) of recently published Y-chromosome data from the Faroe Islands (Jorgensen et al, 2004) also provides evidence for a trend of increased Scandinavian patrilineal ancestry in regions further from the British Isles. The estimated Scandinavian genetic component of the Faroese samples is 87% (N ¼ 89, k ¼ 26), a higher figure than for either Shetland or Orkney.…”
Section: Discussionmentioning
confidence: 83%
“…However, an influx of men and women from the British Isles, either as independent colonisers, or brought there by Vikings, may have contributed significantly to the current gene pool of the Faroese population [15]. It has been suggested that the Faroes were populated by Irish monks or hermits as early as 650 A.D. and they may have left before the Norse settlement [16].…”
Section: The Faroe Islands Include 18 Islands Situated Northwest Of Smentioning
confidence: 99%
“…Based on historical records the establishment of the population was presumably caused by emigration mainly from Bergen and the surrounding area in Norway approximately 900 AD, but people from the British Isles may also have contributed to the colonization of the islands. 18 Based on a genetic study of paternally inherited Y-chromosomes from the Faroese population, it is likely that the Faroe Islands were colonized by males from Norway, Sweden, and Scotland. 18 The population has expanded from a few thousand people to the present level of approximately 45 000 inhabitants, covering periods of constant population size as well as putative periods of population bottlenecks with less than 4000 inhabitants due to severe epidemics.…”
Section: Introductionmentioning
confidence: 99%
“…18 Based on a genetic study of paternally inherited Y-chromosomes from the Faroese population, it is likely that the Faroe Islands were colonized by males from Norway, Sweden, and Scotland. 18 The population has expanded from a few thousand people to the present level of approximately 45 000 inhabitants, covering periods of constant population size as well as putative periods of population bottlenecks with less than 4000 inhabitants due to severe epidemics. 19 Migration has been sparse, 18 and presumably the expansion has mainly been due to increased reproduction rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation